Is There the Holocaust without a Film Music? Analyzing a Croatian and a Serbian Film about the Holocaust - Jambrešić Kirin, Renata (Poznańskie Studia Slawistyczne, 2017)
This article implies that the impact of cinematic fiction on the capability to imagine and comprehend the trauma of the Holocaust is formed at the intersection of aesthetic, moral, social and ideological frames in particular society. Cinema had a special role for the unification of the Holocaust memory since 1990. In the post-Yugoslav cinema two feature films (Lea and Darija, 2011 and When Day Breaks, 2012) represent the cinematic paradigm shift in dealing with the difficult heritage of the Holocaust in Croatia and Serbia following the break of communism. Although they suffer from apolitical approach to historical issues and mitigate the consequences of local collaboration with the Nazis, as well as take the child as „the figure of infantilization” of the Holocaust (Hirsch 2012), their influence on the “postmemory generation” and the pedagogy of trauma in the region is significant and socially relevant.